Fertility Trends in European Countries - Palma, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
This work is intended as an attempt to illustrate and compare the pattern of fertility in European countries: Belarus, Croatia, Hungary, Poland, Portugal, Spain, Sweden, and Switzerland. It deals with the analysis of fertility trends, with an emphasis on birth by parity. Using data from the Human Fertility Database (HFD) from the year 2016, it has considered the parameters of parity progression ratios (PPR), projected parity progression ratios (PPPR), age‑specific fertility rates (ASFR), age‑order specific fertility rates (AOSFR), and cumulated order‑specific fertility rates accordingly analysed. We have applied indicators known as the projected parity progression ratios to estimate trends of fertility. These offer a more detailed view of the family formation process than the traditional total fertility rate (TFR).